Coordination Complex Formation and Redox Properties of Kynurenic and Xanthurenic Acid Can Affect Brain Tissue Homeodynamics - Lenka Kubicova; Franz Hadacek; Gert Bachmann; Wolfram Weckwerth; Vladimir Chobot (MDPI AG, 2019)
Reactive oxygen species (ROS) are known for their participation in various physiological and pathological processes in organisms, including ageing or degeneration. Kynurenine pathway metabolites, such as kynurenic (KYNA) or xanthurenic (XA) acid, can affect neurodegenerative diseases due to their ROS scavenging and Fe ion coordination complex formation but insights are still incomplete. Therefore, we investigated the formation and antioxidant capabilities of KYNA− and XA−Fe complexes by nano-electrospray−mass spectrometry, differential pulse voltammetry, deoxyribose degradation and FeII autoxidation assays. XA formed coordination complexes with FeII or FeIII ions and was an effective antioxidant. By contrast, only FeII−KYNA complexes could be detected. Moreover, KYNA showed no antioxidant effects in the FeCl3/ascorbic acid deoxyribose degradation assay variant and only negligible activities in the FeII autoxidation assay. Coordination complexes of Fe ions with KYNA probably stabilize KYNA in its keto tautomer form. Nevertheless, both KYNA and XA exhibited sufficient antioxidant activities in some of the employed assay variants. The results provide evidence that both have the potential to alleviate neurodegenerative diseases by helping to maintain tissue redox homeodynamics.